2021
DOI: 10.1371/journal.pntd.0009382
|View full text |Cite
|
Sign up to set email alerts
|

Low rate of relapse after twelve-dose multidrug therapy for hansen’s disease: A 20-year cohort study in a brazilian reference center

Abstract: The World Health Organization has raised concerns about the increasing number of Hansen disease (HD) relapses worldwide, especially in Brazil, India, and Indonesia that report the highest number of recurrent cases. Relapses are an indicator of MDT effectiveness and can reflect Mycobacterium leprae persistence or re-infection. Relapse is also a potential marker for the development or progression of disability. In this research, we studied a large cohort of persons affected by HD treated with full fixed-dose mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…This result was similar to findings in Malaysia (18), France (6), and the Ivory Coast (19) but different from findings in China (20) and India (16), where rifampin resistance was more frequent. The frequency of isolated resistance to rifampin and ofloxacin was considered very low, in contrast to results reported in India (7); however, our findings were similar to those in studies by Wahyuni et al (17) and Chen et al ( 5) Our results support the effectiveness of disease control actions according to the WHO-MDT regimen (8).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result was similar to findings in Malaysia (18), France (6), and the Ivory Coast (19) but different from findings in China (20) and India (16), where rifampin resistance was more frequent. The frequency of isolated resistance to rifampin and ofloxacin was considered very low, in contrast to results reported in India (7); however, our findings were similar to those in studies by Wahyuni et al (17) and Chen et al ( 5) Our results support the effectiveness of disease control actions according to the WHO-MDT regimen (8).…”
Section: Discussionsupporting
confidence: 88%
“…Despite these reports, it is still unknown whether AMR affects the maintenance of disease burden. The 12-dose regimen of WHO-MDT is highly effective (8), and it has been successful in the treatment of cases of isolated resistance to dapsone (9). Brazil is among the 23 countries with the highest burdens of the disease, and in 2019, it was responsible for 13.7% of new cases and 43.5% of relapse cases worldwide (2).…”
mentioning
confidence: 99%
“…In retrospect, however, this may not have been required as multiple follow-up studies have demonstrated low rates of relapse with the 12-month regimen which are similar to relapse rates seen with a 24-month regimen [ 23 , 24 ]. The probability of relapse, much like the risk of progression to infection after exposure to M. leprae , is likely related to genetic components that are not entirely understood [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDT has been effective against leprosy and patients are cured after the completion of MDT with low rates of relapses (Nery et al, 2021). Nevertheless, leprosy reactions and permanent disability have been observed in many patients (White and Franco-Paredes, 2015;Nery et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…MDT has been effective against leprosy and patients are cured after the completion of MDT with low rates of relapses (Nery et al, 2021). Nevertheless, leprosy reactions and permanent disability have been observed in many patients (White and Franco-Paredes, 2015;Nery et al, 2021). In this scenario, it is important to better understand why some patients do not have a significant decrease in BI levels, especially because this can be a risk factor for reactional states and consequently high morbidity after release.…”
Section: Discussionmentioning
confidence: 99%